Drug treatments and lifestyle changes in polycystic ovary syndrome (PCOS): A narrative review of the literature (Research, Society and Development, 2025)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder among women of reproductive age. A set of hormonal imbalances, such as increased androgen production and insulin resistance, is responsible for the clinical picture of this condition, including significant dermatological manifestations. So, strategies such as diet, weight control and exercise are used in PCOS therapy, complementing drugs such as oral contraceptives, metformin and antiandrogens. The objective of this systematic review is to analyze the available pharmacological and non-pharmacological treatments for managing hyperandrogenism and the dermatological manifestations associated with PCOS.